2017
DOI: 10.1111/apps.12100
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Side of Employee Referral Bonus Programs: Potential Applicants’ Awareness of a Referral Bonus and Perceptions of Organisational Attractiveness

Abstract: The purpose of this study is to examine the effects of potential applicants’ awareness of employees being rewarded for referrals on organisational attractiveness, based on credibility theory and the multiple inference model. In a first study (N = 450), final‐year students were less attracted to the organisation when they knew employee referrals were rewarded, which was partially explained by lower credibility perceptions. Moreover, varying the specific characteristics of the referral bonus program (i.e. timing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 46 publications
(139 reference statements)
0
13
0
1
Order By: Relevance
“…The completion of the paper-and-pencil survey took about ten minutes. Similar to their own real-life situation, the respondents were asked to imagine themselves as actual job-seekers (e.g., Stockman et al, 2017) before they were shown a job advertisement from a fictitious German retailer ("MARZEO") for a position as a trainee in the corporate headquarter. Companies in the retail industry are particularly suited to research on organizational attraction, as this industry has an expandable employer attractiveness (Rudolph & Runco, 2006).…”
Section: Research Design and Samplementioning
confidence: 99%
See 1 more Smart Citation
“…The completion of the paper-and-pencil survey took about ten minutes. Similar to their own real-life situation, the respondents were asked to imagine themselves as actual job-seekers (e.g., Stockman et al, 2017) before they were shown a job advertisement from a fictitious German retailer ("MARZEO") for a position as a trainee in the corporate headquarter. Companies in the retail industry are particularly suited to research on organizational attraction, as this industry has an expandable employer attractiveness (Rudolph & Runco, 2006).…”
Section: Research Design and Samplementioning
confidence: 99%
“…Thus, it is important to gain knowledge on how their perceived organizational attraction is affected. As a main target group of time-consuming and costly recruiting efforts (Aiman-Smith et al, 2001;Sivertzen et al, 2013) they are a widespread study population in research on organizational attraction (e.g., Stockman et al, 2017). To increase the practical relevance of our sample, we asked 419 business students who were at an advanced stage in their bachelor's program (67%) or master's program (33%) to participate in this study, as they would soon be entering the labor market (e.g., Stockman et al, 2017).…”
Section: Research Design and Samplementioning
confidence: 99%
“…Örgütsel çekicilik son yıllarda dikkatleri üzerine çeken bir kavram olarak göze çarpmaktadır (Güler ve Basım, 2015;Lambert, Basuil, Bell ve Marquardt, 2017;Lievens, Van Hoye ve Schreurs, 2005;Nolan ve Harold, 2010;Stockman, Van Hoye ve Carpentier, 2017). Örgütlerin potansiyel çalışma adaylarının ve mevcut çalışanlarının örgütte devam etme istekliliklerini güçlendirmesi, örgüte duyulan çekicilik algısı ile ilişkilidir.…”
Section: Introductionunclassified
“…We manipulated promising a referral bonus by mentioning that employees receive a €500 referral bonus for a successful referral versus mentioning nothing about rewarding referrals. The bonus amount was based on input from HR managers from the healthcare sector and a previous study on referral bonuses (Stockman, Van Hoye, & Carpentier, 2017). In the autonomous referral request with a referral bonus, the bonus was positioned at the end of the e‐mail and framed as a way to thank the nurses in case they would refer.…”
Section: The Studymentioning
confidence: 99%